RESEARCH ON CHILDREN’S CULTURAL CREATIVE PRODUCTS OF MARINE CULTURE TOURISM BASED ON EXPERIENCE DESIGN CASE STUDY: QINGDAO, CHINA. - Xiaoshuo Jiang; S’harin Mokhtar (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The growth of marine tourism in China has resulted in the establishment of a sector that can currently support its own financial needs. There has been a growth in the total amount of money that can be attributed to tourism as a result of the ever-growing tourism culture. A great number of the cities that are located near the shore are significantly reliant on the revenue that is generated by tourism. The major focus of the discussion in this article will be on the cultural and creative products that may be generated through maritime tourism. This study was carried out in order to clarifies its design in detail research paths to promote the active application and development of marine tourism cultural resources by analyzing the current status and problems of its tourism children’s cultural products, as well as the situation of the marine tourism cultural creative industry in Qingdao.